Endocardial Left Atrial Appendage Occlusion in Atrial Fibrillation: Device Design, Clinical Evidence, and Postprocedural Antithrombotic Management - Grigory Matvienko; Mantė Agnė Rimkienė; Vilhelmas Bajoras; Agnė Drąsutienė; Rūta Masiulienė; Dovilė Gabartaitė; Monika Šalaševičienė; Mindaugas Matačiūnas; Diana Sudavičienė; Germanas Marinskis; Audrius Aidietis; Gediminas Račkauskas (Medicina, 2026)
Background and Objectives: Atrial fibrillation is a major cause of ischemic stroke, and in patients with non-valvular atrial fibrillation the left atrial appendage is the predominant site of thrombus formation. Although oral anticoagulation remains the standard strategy for stroke prevention, long-term therapy may be limited by bleeding risk, prior major bleeding, contraindications, intolerance, or difficulty maintaining stable anticoagulation. Endocardial left atrial appendage occlusion (LAAO) has therefore emerged as an alternative strategy in selected patients. Its role continues to evolve with expanding device technologies, contemporary direct oral anticoagulant therapy, and ongoing randomized evidence. Materials and Methods: This narrative literature review summarizes current evidence on endocardial LAAO, focusing on device design, anatomical considerations, clinical outcomes, postprocedural antithrombotic therapy, and ongoing research directions. Results: Available devices differ substantially in sealing mechanism, fixation strategy, conformability, surface properties, and suitability for complex appendage anatomy. The Watchman and Amulet platforms remain the most extensively studied systems, whereas several CE-marked and investigational devices aim to improve anatomical adaptability, reduce peri-device leak and device-related thrombus, and simplify implantation. Randomized evidence supports LAAO as a non-inferior alternative to oral anticoagulation in selected populations, with potential reduction in late bleeding but persistent concerns regarding procedural risk, frailty, comorbidity burden, and patient selection. The optimal postprocedural antithrombotic regimen remains uncertain, with increasing interest in individualized strategies and short-term direct oral anticoagulant therapy when feasible. Current research is shifting toward next-generation devices, combined ablation–closure strategies, simplified imaging guidance, and evaluation of LAAO as both an alternative and an adjunct to oral anticoagulation. Conclusions: LAAO should currently be considered a selective rather than a universal strategy, requiring individualized assessment of thromboembolic risk, bleeding risk, anatomy, procedural safety, and comorbidity burden.